1998
DOI: 10.1002/(sici)1520-6327(1998)37:1<91::aid-arch11>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel oxadiazine insecticide is bioactivated in lepidopteran larvae

Abstract: DPX‐JW062 is a new insecticide showing strong field activity, especially on Lepidoptera. Metabolism studies in several lepidopteran larvae show that orally administered [14C]DPX‐JW062 is rapidly cleaved to a decarbomethoxyllated metabolite (DCJW), based upon HPLC and mass spectrometry identification. The metabolic conversion is correlated with appearance of neurotoxic symptoms. Tissue localization studies with fifth instar Manduca sexta larvae have shown that the fat body and especially midgut are the most act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(40 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…5 Metabolism studies in Lepidoptera have shown that indoxacarb is bioactivated by an esterase or amidase type of enzyme(s) to the active N-decarbomethoxyllated metabolite, which blocks voltage-dependent sodium channels, preventing influx of sodium into neurons and resulting in insect paralysis and death. 5,6 Indoxacarb is among the most recent compounds to be used for control of H. armigera in Australia, and resistance to indoxacarb has been monitored since it was introduced in 2002. From 2002 to 2012, field resistance was determined from traditional screening methods involving topical application of a discriminating concentration of insecticide to larvae in the F 0 generation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Metabolism studies in Lepidoptera have shown that indoxacarb is bioactivated by an esterase or amidase type of enzyme(s) to the active N-decarbomethoxyllated metabolite, which blocks voltage-dependent sodium channels, preventing influx of sodium into neurons and resulting in insect paralysis and death. 5,6 Indoxacarb is among the most recent compounds to be used for control of H. armigera in Australia, and resistance to indoxacarb has been monitored since it was introduced in 2002. From 2002 to 2012, field resistance was determined from traditional screening methods involving topical application of a discriminating concentration of insecticide to larvae in the F 0 generation.…”
Section: Introductionmentioning
confidence: 99%
“…18 The compound is bioactivated by insects to the potent sodium channel blocker DCJW (which stands for decarbomethoxylated DPX-JW062, or DCMP if the proinsecticide is enantiomerially enriched DPX-MP062) via an N-decarbomethoxylation enzymatic cleavage. 19,20 However, indoxacarb is broken down quite extensively by mammals and is exceptionally safe. 21 Later, another SCBI insecticide, metaflumizone, was commercialized by Nihon Noyaku, BASF and Pfizer Animal Health.…”
Section: Dihydropyrazoles To Indoxacarb -Engineering Mammalian Safetymentioning
confidence: 99%
“…Chiral pesticides with specificity and environmental safety have captured continuously with wide attention in agriculture, 1,2 because of the emphasis on environmental pollution and the advocacy of green chemistry. Indoxacarb (see Figure 1 for structure), a new chiral oxadiazine pro-insecticide, 3 being converted into the active compound by removal of a CO 2 Me in the insect gut (discovered and developed by the E.I. DuPont Company), has shown to possess high activity, commercial availability, and environmental compatibility to administered to lepidopteran and hemipteran pests.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the S-enantiomer of indoxacarb is active as the racemate in insects, while the R-enantiomer is inactive. 3 Therefore, the synthesis of (S)-5-chloro-1-oxo-2,3-dihydro-2-hydroxy-1H-indene-2-carboxylic acid methyl ester has sparked heated interest in the pesticide industry.…”
Section: Introductionmentioning
confidence: 99%